Children and Adolescents’ Ingroup Biases and Developmental Differences in Evaluations of Peers Who Misinform - Farooq, Aqsa; Ketzitzidou Argyri, Eirini; Adlam, Anna; Rutland, Adam (Frontiers in Psychology, 2022)
Previous developmental research shows that young children display a preference for ingroup members when it comes to who they accept information from – even when that information is false. However, it is not clear how this ingroup bias develops into adolescence, and how it affects responses about peers who misinform in intergroup contexts, which is important to explore with growing numbers of young people on online platforms. Given that the developmental span from childhood to adolescence is when social groups and group norms are particularly important, the present study took a Social Reasoning Developmental Approach. This study explored whether children and adolescents respond differently to a misinformer spreading false claims about a peer breaking COVID-19 rules, depending on a.) the group membership of the misinformer and their target and b.) whether the ingroup had a ‘critical’ norm that values questioning information before believing it. 354 UK-based children (8 – 11 years old) and adolescents (12 – 16 years old) read about an intergroup scenario in which a peer spreads misinformation on WhatsApp about a competitor. Participants first made moral evaluations, which asked them to judge and decide whether or not to include the misinformer, with follow-up “Why?” questions to capture their reasoning. This was followed by asking them to attribute intentions to the misinformer. Results showed that ingroup preferences emerged both when participants morally evaluated the misinformer, and when they justified those responses. Participants were more likely to evaluate an ingroup compared to an outgroup misinformer positively, and more likely to accuse an outgroup misinformer of dishonesty. Adolescents attributed more positive intentions to the misinformer compared with children, with children more likely to believe an outgroup misinformer was deliberately misinforming. The critical norm condition resulted in children making more positive intentionality attributions towards an ingroup misinformer, but not an outgroup misinformer. This study’s findings highlight the importance of shared group identity with a misinformer when morally evaluating and reasoning about their actions, and the key role age plays in intentionality attributions surrounding a misinformer when their intentions are ambiguous.